Rethinking Language Education and Teacher Preparation - Yadav, Saryug; Paliwal, Anil (JOURNAL OF INDIAN EDUCATION, 2021)
Language has always been a key concern in the field of education. Due to the rapid advancement of science and technology in the existing era there is an increased mobility and, therefore, communication between and among people of different spheres of life is crucial. Globalisation demands that an educated person should not only possess knowledge and a knack but also should be wellversed in the art of communication. A mere traditional way of teaching languages may not be adequate to ensure the quality upgradation in language education aimed at developing the desired outcomes in multilingual, multicultural and multi-ethnic society. Language education necessitates rethinking in the present globalised world as it is a pre-requisite for all education. Globalisation which was initially conceptualised in the context of economy, has gradually enveloped various dimensions of our life encompassing the whole of our knowledge and society. Globalisation has made enormous impact in the input process and product of language education in general and instruction and learning in particular. India is a multilingual country with several languages and dialects. Multilingualism presents a challenging issue in the schooling context. It also refers to a situation in which more than one language is used in or out-of-school setting. Developing a language curriculum for a multilingual country like India is a tough task. The present paper intends to reconsider language curriculum and pedagogy for Indian schools in a multilingual, multicultural and multiethnic context with an aim to exploring and explaining an operative model of language education in the era of globalisation.